2011
DOI: 10.1128/jvi.05806-11
|View full text |Cite
|
Sign up to set email alerts
|

Satellite RNA-Derived Small Interfering RNA satsiR-12 Targeting the 3′ Untranslated Region of Cucumber Mosaic Virus Triggers Viral RNAs for Degradation

Abstract: RNA silencing provides protection against RNA viruses by targeting both the helper virus and its satellite RNA (satRNA). Virus-derived small interfering RNAs (vsiRNAs) bound with Argonaute (AGO) proteins are presumed participants in the silencing process. Here, we show that a vsiRNA targeted to virus RNAs triggers the host RNA-dependent RNA polymerase 6 (RDR6)-mediated degradation of viral RNAs. We confirmed that satRNA-derived small interfering RNAs (satsiRNAs) could be associated with different AGO proteins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 54 publications
(89 reference statements)
0
39
0
3
Order By: Relevance
“…Moreover, using CMV-Δ2b-infected transgenic plants expressing asatsiR-12, we found that asatsiR-12 was able to reduce the accumulation of CMV RNAs. Also, we verified that asatsiR-12-mediated reduction of viral RNAs in the presence of RDR6 was inhibited by the 2b suppressor [48]. A high concentration of replicating satRNAs could reduce the accumulation of viral RNAs in N. benthamiana on later infection by CMV-2b [49].…”
Section: Molecular Basis Of the Vsirna-mediated Antiviral Effectmentioning
confidence: 61%
See 3 more Smart Citations
“…Moreover, using CMV-Δ2b-infected transgenic plants expressing asatsiR-12, we found that asatsiR-12 was able to reduce the accumulation of CMV RNAs. Also, we verified that asatsiR-12-mediated reduction of viral RNAs in the presence of RDR6 was inhibited by the 2b suppressor [48]. A high concentration of replicating satRNAs could reduce the accumulation of viral RNAs in N. benthamiana on later infection by CMV-2b [49].…”
Section: Molecular Basis Of the Vsirna-mediated Antiviral Effectmentioning
confidence: 61%
“…By introducing mutations into the region generating satsiR-12, we confirmed that satsiR-12 was indeed involved in the satRNA-mediated reduction in CMV RNAs. Our findings provided the first demonstration that viral satellite RNA-derived siRNAs could mediate silencing against their helper virus [48].…”
Section: Molecular Basis Of the Vsirna-mediated Antiviral Effectmentioning
confidence: 91%
See 2 more Smart Citations
“…There are many examples of animal lncRNAs that control chromatin modifications. mechanism may still be true, Zhu et al (2011) demonstrated another possibility, that siRNAs derived from CMV satRNAs could target the 3 untranslated region in CMV genomic RNAs for cleavage of CMV RNAs, which then triggers RDR6-dependent secondary siRNA amplification, resulting in a decrease of CMV accumulation. Their results suggest that satRNA can attack the helper virus through the plant's major defense system, RNA silencing, and thus strengthen the defense response against viruses in plant cells.…”
Section: Mechanism Of CMV Satrnas To Enhance Host Defensementioning
confidence: 98%